1988
DOI: 10.1037/0022-3514.55.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Major life events, hassles, and adaptation in adolescence: Confounding in the conceptualization and measurement of life stress and adjustment revisited.

Abstract: Prior work has suggested that methodological and conceptual confounding may play a role in the associations obtained between stressful life events, social resources, and adaptive outcome. Of particular concern in our work were (a) the source and method of assessment; (b) conceptual overlap between life stress and resource items and symptoms of disorder; and (c) induced response bias through the instructional sets of the stress measures. A second goal was to extend our understanding of the life stress-adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
162
1
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(175 citation statements)
references
References 41 publications
9
162
1
3
Order By: Relevance
“…Major events include infrequent but significant events such as the death of a family member, the loss of a job, or divorce. Although daily stressors are conceptually distinct from life events in their predictive ability and effects on health and well-being, they are related to one another (Rowlison & Felner, 1988). In addition, daily stressors are often the sequelae to life events and the reason why people experience psychosocial distress in response to major life events (Wagner, Compas, & Howell, 1988).…”
Section: Insight From Research On Life Eventsmentioning
confidence: 99%
“…Major events include infrequent but significant events such as the death of a family member, the loss of a job, or divorce. Although daily stressors are conceptually distinct from life events in their predictive ability and effects on health and well-being, they are related to one another (Rowlison & Felner, 1988). In addition, daily stressors are often the sequelae to life events and the reason why people experience psychosocial distress in response to major life events (Wagner, Compas, & Howell, 1988).…”
Section: Insight From Research On Life Eventsmentioning
confidence: 99%
“…Once Ryan and Deci (2000) established that trait-and domain-specific levels of autonomy, competence, and relatedness were significantly associated with well-being, it was important for researchers to consider whether daily fluctuations in these three needs would have a similar impact on daily well-being. Using the diary-study methodology, previous researchers have found that negative events such as daily hassles (Rowlison & Felner, 1988) and stressors (Mroczek & Almeida, 2004) have a negative impact on well-being. Subsequently, SDT researchers reasoned that the positive experience of satisfying the basic needs should positively affect well-being.…”
Section: Satisfaction Of Needs and Well-beingmentioning
confidence: 99%
“…O stress quotidiano refere-se a acontecimentos que o indivíduo avalia como representando um desafio, ameaça ou possível perda, e que implicam uma reação afetiva negativa, por exemplo gerando ansiedade ou reações depressivas. Estas situações associam-se, também, a um baixo controlo percebido (Rowlison & Felner, 1988;Lazarus, 1995). A escola ocupa um lugar de relevo na vida de crianças e adolescentes.…”
unclassified